Community, Frame of Reference, and Boundary: Three Sociological Concepts and their Relevance for Virtual Worlds Research - Williams, J. Patrick Williams (Qualitative Sociology Review, 2009)
Virtual-worlds research is a dynamic and growing interdisciplinary area in the social sciences and humanities. Sociological theory can play an important role in how virtual worlds are conceptualized and studied. Drawing on data from ethnographic projects on two distinct types of virtual worlds, an asynchronous text-based internet forum and a massively-multiplayer online game, I consider what social and cultural similarities these two types of virtual worlds have with one another, despite their radically different forms and functions. My comparative analysis is framed in terms of three questions. First, are virtual worlds temporary and/or intentional communities? Second, what are the frames of reference through which virtual-world communities are built? Third, how do boundaries function in virtual worlds? My discussion suggests some of the common social and cultural features of virtual worlds.